The interpretation of "in context" verbal probability expressions used in international financial reporting standards: Evidence from Poland - Jerzy Gierusz; Katarzyna Kolesnik; Sylwia Silska Gembka (European Financial and Accounting Journal, 2019)
The objective of this paper is to specify in which way Polish accounting professionals manage to interpret 'in context' verbal probability expressions (VPEs) from IFRS. Taking into account the Polish accounting professionals attachment to the prudence principle and the Polish mindset, we research here whether they have a conservative approach when interpreting those expressions. For the purpose of our study we distributed a questionnaire and asked a sample of accountants and auditors from Poland to interpret the term 'probable' used in IFRS to establish the threshold for recognition of various accounting elements. Our findings provide evidence that the differences in interpretation of 'in context' VPEs by Polish accounting professionals exist. We also find that the level of conservatism shared by Polish accountants and auditors affects their individual accounting judgment.
Keywords: M41; 650; Financial reporting; IFRS; Interpretation; Professional judgment; Verbal probability expressions